Pemanfaatan media sosial sebagai media penyajian konten edukasi atau pembelajaran digital - Yuni Fitriani (Journal of Information System, Applied, Management, Accounting and Research, 2021)
The development of information and communication technology provides many changes in people's lives. Where nowadays people can access the internet easily and interact with various social media sites. Social media can not only be used for communication tools, but also has many functions for the community, one of which is that it can be used as a medium for presenting digital learning content. The use of social media as a medium of presentation of educational content or digital learning can help identify additional learning content, expand learning materials and be able to share knowledge with other users on social media. In this study, the social media studied were Instagram, Facebook, YouTube and TikTok. The research method used is a semi-descriptive quantitative method to explain an existing phenomenon by using numbers to describe or describe the characteristics of something and assess the nature of the conditions that appear. Social media platforms such as Instragram, Facebook, YouTube and TikTok can be used as a presentation medium for educational content or digital learning. Where the use of social media as a presentation media for digital educational content helps its users in adding new knowledge and insights